Incorporation sunpaths for solar analysis in the 3DSkyView extension. - Souza, Léa Cristina Lucas (2005)
The 3DSkyView extension was recently created to estimate sky view factors (SVF) of urban canyons. In a second version it was made possible the calculation of simultaneous SVF for many viewpoints. Now in the third version the user is able to visualize sunpath diagrams along with the representation of the sky view factor. By applying the extension, a case study was carried out allowing the identification of thermal tendencies within a neighborhood.